2013
DOI: 10.3758/s13428-012-0290-1
|View full text |Cite
|
Sign up to set email alerts
|

On using isoluminant stimuli to separate magno- and parvocellular responses in psychophysical experiments—A few words of caution

Abstract: Isoluminant (or equiluminant) color stimuli (i.e., those that contain variations only in chromaticity) have been employed in attempts to separate magno-and parvocellular responses in psychophysical and noninvasive electrophysiological experiments. The justification for this has been the assumption that magnocellular cells, unlike parvocellular neurons, do not respond to stimuli varying only in hue. However, several problems are associated with this notion: (1) under many conditions, magnocellular neurons are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…With the idea of testing this hypothesis in mind, we presented emotional and neutral stimuli under two modalities: isochromatic/heteroluminant stimuli and heterochromatic/isoluminant. These parameters have been reported to be M and P balanced, respectively (e.g., Livingstone & Hubel, 1988), enhancing the involvement of one visual system (P or M) over the other (but not completely suppressing any, since P and M systems may respond similarly to isoluminant stimuli under certain circumstances: see a review in Skottun, 2013). A recent study (not exploring spatial location) reported that isochromatic/heteroluminant (i.e., M balanced) emotional stimuli presented in the periphery captured attention to a greater extent than both P balanced emotional stimuli and M balanced neutral stimuli (Carretié et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the idea of testing this hypothesis in mind, we presented emotional and neutral stimuli under two modalities: isochromatic/heteroluminant stimuli and heterochromatic/isoluminant. These parameters have been reported to be M and P balanced, respectively (e.g., Livingstone & Hubel, 1988), enhancing the involvement of one visual system (P or M) over the other (but not completely suppressing any, since P and M systems may respond similarly to isoluminant stimuli under certain circumstances: see a review in Skottun, 2013). A recent study (not exploring spatial location) reported that isochromatic/heteroluminant (i.e., M balanced) emotional stimuli presented in the periphery captured attention to a greater extent than both P balanced emotional stimuli and M balanced neutral stimuli (Carretié et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…What must be borne in mind is that all these studies were conducted in optimal luminance environments (ratios have been tested in a range from 0.4 tõ 70 cd/m 2 ). Despite claiming to isolate magnocellular pathways, the luminance range is too broad (especially >1 cd/m 2 ) incorporating parvocellular spectral ranges, which may confound assumptions about the parvocellular contribution to the identification or search process (Skottun, 2013) or vice versa. Also, and probably most importantly, it is recognized that true isoluminance may never be fully established in the lab setting (Braithwaite, Watson, Andrews, & Humphreys, 2010;Skottun, 2013), which makes comparisons between studies difficult.…”
Section: Absolute Luminance and Luminance Contrastmentioning
confidence: 99%
“…Despite claiming to isolate magnocellular pathways, the luminance range is too broad (especially >1 cd/m 2 ) incorporating parvocellular spectral ranges, which may confound assumptions about the parvocellular contribution to the identification or search process (Skottun, 2013) or vice versa. Also, and probably most importantly, it is recognized that true isoluminance may never be fully established in the lab setting (Braithwaite, Watson, Andrews, & Humphreys, 2010;Skottun, 2013), which makes comparisons between studies difficult. Furthermore, the contribution of absolute luminance or luminance contrast may be more crucial under low mesopic environments due to the difference in the inherent perceptual responsiveness of the main visual pathways within this range.…”
Section: Absolute Luminance and Luminance Contrastmentioning
confidence: 99%
“…Both of them contained colour information, thus they drove the P pathway. The subjective isoluminant stimulus is known for driving most selectively the P pathway (Skottun, 2013), but because of the inter individual differences regarding the point of isoluminant level the measured luminance differences between the background and stimuli showed different contrast values so we used a physical isoluminant condition as well containing only colour contour between the stimuli and the background.…”
Section: Figure 1 Illustration Of Stimulus Presentation In Central Amentioning
confidence: 99%
“…The physically isoluminant stimuli have only color information, but the different colors drive the visual system with different strength. The subjective isoluminant stimulus is known as it can drive most selectively the P pathway (Skottun 2013). In the peripheral task a fixation point was placed in the middle of the screen and the stimulus disc was presented it at 9.25° eccentricity ).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%